(untitled) (Research, Society and Development, 2020)
This study aimed to investigate factors associated with anxiety and depression in university students. A quantitative, cross-sectional and observational study realized with 1245 adults, university students from different areas of knowledge from a higher education institution in northwest Paraná participated. A questionnaire prepared by the authors with questions related to sex, age, area of ​​the course, and year they were enrolled was used. As an instrument, the Hospital Scale of “Anxiety and Depression” (HAD), adapted for the educational scope, was used. Data analysis was performed using the Kolmogorov-Smirnov, Kruskal-Wallis and Mann-Whitney and Chi-square tests (p<0.05). The results showed that students with a probable depression classification (Md = 24.3) had a higher body mass index (BMI) than students with an unlikely (Md = 23.0) and possible (Md = 23.5). There was a higher proportion of students with probable anxiety and depression among women (77.7%) and students in the humanities and social fields (65.6%). It was concluded that BMI, sex and the area of knowledge seem to be associated with anxiety and depression in university students.